Advanced applications of periodic fibre structures in chemical sensing - Tan, Rex Xiao (Nanyang Technological University, 2020)
Optical fibres had found applications in a wide range of engineering fields including but not limited to manufacturing, medical technology and structural monitoring since its discovery. With the maturity of optical fibre technology and demand to monitor the environment, optical fibre environmental sensors received increased attention. Optical fibres can detect changes in its environment in the form of refractive index (RI), temperature, strain and other perturbances. Changes in environmental RI is particularly of interest to this thesis as it can be indicative of pollution amongst other issues. Furthermore, optical fibre sensitivity of RI can be exploited for sensing selected chemicals with simple surface coatings, enabling targeted chemical sensing in the environment. This thesis presents two new fibre Bragg grating (FBG) based RI sensing schemes designed to address the issues of temperature and strain cross-sensitivity that are plaguing most state-of-the-art fibre RI sensors. Both proposed schemes can measure RI and temperature simultaneous with no cross-sensitivity effect. The first of the sensing scheme adopts a low finesse Fabry-Perot (FP) cavity formed between an FBG and the cleaved end of the optical fibre, with the cleaved fibre end as the sensing interface. This sensor measures the RI through the modulation of the resulting FP interference while measuring temperature change from spectral shifts. A maximum RI sensitivity of 230dB/RIU in the RI range of 1.333 to 1.471 and temperature sensitivity of 8.43pm/ºC were achieved. The second scheme makes use of a birefringent FBG inscribed into a special C-shaped birefringent optical fibre where one polarisation mode is purposefully exposed to the environment. The birefringence of this special fibre is affected by changes in environmental RI and causes spectral response to the birefringent FBG in the form of polarisation mode separation, while temperature change induces a common spectral shift regardless of polarisation. A maximum RI sensitivity of 1300pm/RIU in the RI range of 1.333 to 1.410 was achieved. Work on the first RI sensing scheme was further explored by coating the sensing fibre end with Ethylenediaminetetraacetic acid (EDTA) and Molybdenum disulphide (MoS2) for heavy metal ion in water and ethylene gas sensing respectively. Both the sensors achieved high sensitivity, being able to detect traces of heavy metal ion in water from 10ppm and ethylene gas from 500ppb.